Aid and domestic resource mobilisation with a focus on sub-Saharan Africa - Morrissey, Oliver (Oxford University Press, 2015)
Increasing tax revenues in low income countries is essential to address future development finance requirements. This is particularly important for aid recipients, the focus of this paper. Theory shows that although there are many ways in which aid can have indirect effects on tax revenue, the direct effects arise because aid and tax are alternative sources of revenue and political economy factors influence the choices made by government. Aid may discourage tax effort if viewed as a politically less costly source of revenue. Under different conditions, the policies and reforms associated with aid may increase revenue, through promoting growth, encouraging more efficient tax structures or supporting reforms to tax administration. While cross-country evidence reveals no systematic pattern, country studies show that aid can be associated with administrative and efficiency reforms to increase tax revenue. The conclusion discusses how aid and donors can promote increasing domestic tax revenue.